2022
DOI: 10.5194/bg-19-559-2022
|View full text |Cite
|
Sign up to set email alerts
|

Representativeness assessment of the pan-Arctic eddy covariance site network and optimized future enhancements

Abstract: Abstract. Large changes in the Arctic carbon balance are expected as warming linked to climate change threatens to destabilize ancient permafrost carbon stocks. The eddy covariance (EC) method is an established technique to quantify net losses and gains of carbon between the biosphere and atmosphere at high spatiotemporal resolution. Over the past decades, a growing network of terrestrial EC tower sites has been established across the Arctic, but a comprehensive assessment of the network's representativeness w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Eurasia contributed to a majority (74%) of the boreal NEE sink, and the largest CO 2 sink by area was observed in the larch‐dominated East Siberian Taiga. Although the geographically extensive Eastern Siberian Taiga remains largely underrepresented by EC tower monitoring sites (Pallandt et al, 2022), this region has been identified as an important, perhaps increasing, carbon sink (Byrne, Liu, et al, 2022; Lin et al, 2020; Sato et al, 2016; Schulze, 2006). However, elevated fire activity here in recent years (post‐2015) (Veraverbeke et al, 2021) might now be offsetting more of the carbon uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Eurasia contributed to a majority (74%) of the boreal NEE sink, and the largest CO 2 sink by area was observed in the larch‐dominated East Siberian Taiga. Although the geographically extensive Eastern Siberian Taiga remains largely underrepresented by EC tower monitoring sites (Pallandt et al, 2022), this region has been identified as an important, perhaps increasing, carbon sink (Byrne, Liu, et al, 2022; Lin et al, 2020; Sato et al, 2016; Schulze, 2006). However, elevated fire activity here in recent years (post‐2015) (Veraverbeke et al, 2021) might now be offsetting more of the carbon uptake.…”
Section: Discussionmentioning
confidence: 99%
“…scale, ABR are notoriously underrepresented in this network (Fig. 1; Baldocchi et al, 2001;Pastorello et al, 2020;Pallandt et al, 2022). Satellite remote sensing and terrestrial biosphere models show promise for monitoring land surface-atmosphere interactions across ABR (Fisher et al, 2018;Lees et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, spaceborne visible and infrared radiometers are affected by signal degradation from atmospheric effects, have minimal signal penetration depth in vegetation, and depend on solar illumination meaning they are restricted to daytime, clear sky observations (Kim et al, 2012). 90 (Brown et al, 2002) and distribution of eddy covariance sites where ecosystem fluxes are monitored continuously (Baldocchi et al, 2001 andPallandt et al, 2022; dot size represents the number of years of available data). The Arctic biome is delineated following the Conservation of Arctic Flora and Fauna working group of 95 the Arctic Council and the boreal biome is delineated following Potapov et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, Tao et al (2021) found an annual net CO 2 flux range of -9 to 12 TgC yr -1 for the years 2010-2016, with only 2014 being an annual net CO 2 source. Extrapolating from sitelevel CO 2 flux measurements to regional budgets is difficult due to the extreme heterogeneity of tundra ecosystems in the North Slope and a lack of spatial and seasonal representativeness by existing flux monitoring sites (Pallandt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%